The economy of India and a modern version from the present to the future - Fathullah Jasim Mustafa3Fekri Ahmed Lahmood*1,; Khaleel Abd, Mustafa Ismaeel (Opción, 2019)
The present research paper aims mainly to study the issue of globalization from a present and future perspective. As a result, the paper will focuses on practical study at India state regarding some major factors affecting positively or negatively on the overall economic due to the distribution of the globalization. Through the study, we found that the Indian government provided facilities for foreign companies to encourage the growing economy. In conclusion, opportunities and challenges will emerge as a natural consequence of shifts in environments from the political, security, regional and global security perspectives